The Mustahik Zakat in Various Dimensions of Fiqh in Era Society 5.0 - Desi Refnita (El-Mashlahah, 2021)
This article will discuss mustahik zakat, who are the groups who will receive "mustahik" zakat, and what are the conditions for recipients (mustahik) zakat and who are not entitled to receive zakat in era society 5.0. Mustahik zakat is people who are entitled to receive zakat assets. Groups of zakat recipients, namely, needy, poor, who organize and deliver, converts, slave servants, people in debt, fi Sabilillah, and traveling (Ibnu Sabil). We conducted literature studies, and descriptive analysis approaches the theory and reality in distributing zakat from various thought reviews schools. According to Imam Syafi'i, people who are in debt are also entitled to receive zakat. However, not everyone who owes a lot is entitled to receive zakat. This paper is taken from several references on zakat fiqh, especially mustahik zakat. It is developed in the discussion of zakat recipients such as leaders with weak faith or non-Muslims who are feared that it will create chaos. Acceptance and payment of zakat are more transparent, and era society 5.0 is in line with technological developments. It is hoped that the amount of zakat collection and distribution will be maximized.